Analysis of gender wage differences and their determinants in the Czech Republic - Babjaková, Miriam; Kalíšková, Klára; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
This diploma thesis focuses on analysis of gender wage differences and their determinants in the Czech Republic. The gender wage differences were analysed by aggregated data, microdata for employees from the survey Statistics on Income and Living Conditions for the year 2018 and by data about employees of company (which name is kept anonymous) operating in financial sector in the Czech Republic. In the main analysis, which used data of employees from Statistics on Income and Living Conditions 2018, the adjusted gender wage gap was estimated for employees to 24.9%. Thus, 20.5% of gender wage gap was explained by explanatory variables. It was found that number and age of children has an impact on gender wage differences. The gender wage gap for average yearly earnings is for employees with child younger than 6 years old 47.3%, which is higher by 26.7 pp. than gender wage gap for employees without children. The gender wage differences present in the analysed company operating in financial sector was decomposed by Oaxaca-Blinder decomposition to 51.2% of explained part and 48.8% of unexplained part.
Vedoucí práce: Klára Kalíšková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses